Patient Safety Culture in Pre-Post Partum and Perinatology Units - Suci, Wice Purwani; Erika, Erika; Lestari, Widia; T, Nurhannifah Rizky; Maria, Riamin; Sunairattanaporn, Usa (Jurnal Pendidikan Keperawatan Indonesia, 2024)
Introduction: Effective patient safety practices in pre-post partum and perinatology units are crucial for ensuring high-quality care for mothers and children. These practices are expected to reduce maternal and child mortality rates, which remain significant. Patient safety implementation in hospitals depends largely on the patient safety culture within each institution. Objective: This study aimed to assess the application of patient safety culture in pre-post partum and perinatology wards. Methods: The research employed a mixed-methods approach with a sequential explanatory design. Quantitative data were gathered using the AHRQ (Agency for Health Research and Quality) questionnaire. Meanwhile, the qualitative research used an instrumental case study approach insights were derived from in-depth interviews with 52 nurses working in these units. Results: Results show an overall positive response rate of 67.8% across the 12 dimensions of patient safety culture, indicating satisfactory levels. The dimension with the highest positive response rate is teamwork at 38%, while openness had the lowest at 6%. Challenges in patient safety program implementation include lack of safety culture surveys, inadequate incident reporting systems, high blaming culture, lack of support, delayed case reporting, and financial constraints. Reporting, analysis, and evaluation are predominantly limited to internal hospital processes. Conclusion: The obstacles encountered in implementing a patient safety culture are the behavior of healthcare workers and the lack of optimal support from management. The recommendations given are the formation of a Patient Safety Committee, education about safety culture for healthcare workers, Monitoring and evaluation of the patient safety program that has been implemented.